Stroke rehabilitation evidence and comorbidity: a systematic scoping review of randomized controlled trials. Issue 5 (4th July 2017) - Nelson, Michelle L. A.; McKellar, Kaileah A.; Yi, Juliana; Kelloway, Linda; Munce, Sarah; Cott, Cheryl; Hall, Ruth; Fortin, Martin; Teasell, Robert; Lyons, Renee
Abstract: Background : Most strokes occur in the context of other medical diagnoses. Currently, stroke rehabilitation evidence reviews have not synthesized or presented evidence with a focus on comorbidities and correspondingly may not align with current patient population. The purpose of this review was to determine the extent and nature of randomized controlled trial stroke rehabilitation evidence that included patients with multimorbidity. Methods : A systematic scoping review was conducted. Electronic databases were searched using a combination of terms related to "stroke" and "rehabilitation." Selection criteria captured inpatient rehabilitation studies. Methods were modified to account for the amount of literature, classified by study design, and randomized controlled trials (RCTs) were abstracted. Results : The database search yielded 10771 unique articles. Screening resulted in 428 included RCTs. Three studies explicitly included patients with a comorbid condition. Fifteen percent of articles did not specify additional conditions that were excluded. Impaired cognition was the most commonly excluded condition. Approximately 37% of articles excluded patients who had experienced a previous stroke. Twenty-four percent excluded patients one or more Charlson Index condition, and 83% excluded patients with at least one other medical condition. Conclusions : This review represents a first attempt to map literature on stroke rehabilitation related to co/multimorbidity and identify gaps in existing research. Existing evidence on stroke rehabilitation often excluded individuals with comorbidities. This is problematic as the evidence that is used to generate clinical guidelines may not match the patient typically seen in practice. The use of alternate research methods are therefore needed for studying the care of individuals with stroke and multimorbidity.